Roads to competitiveness : human development with export growth : the Caribbean challenge - Hasham, M.F. ed. (Univ. of the Netherlands Antilles [Willemstad]AN)
Deals with how to create a competitive base for income generation and employment and at the same time insure the necessary quality of life for the Caribbean people.